Examination of Stereotactic Mammotome Biopsy for Microcalcification in Our Hospital - Sueoka, Noriko; Ishizuka, Mariko; Yoshikawa, Katsuhiro; Tsubota, Yu; Yamamoto, Daigo; Kon, Masanori (Gan to kagaku ryoho, 2017)
We introduced stereotactic mammotome biopsy(ST-MMT)for the purpose of screening and other institutions. There are many benign cases to be diagnosed by pathological findings, so it is thought to be necessary to examine the adaptation of STMMT again. We examined the performance of ST-MMT in a case of a non-palpating calcification lesion. Between August 2013 and December 2016, ST-MMT biopsies were performed for 247 microcalcified lesions revealed by mammography(in both breasts in 9 patients; twice in the ipsilateral breast in 2 patients). The mean age of all patients was 46 years(range, 24- 89 years). We found 39 cases(15.8%)of breast cancer. A final diagnosis of breast cancer was made in 39 patients, who comprised 0% of those with Category 2, 53.8% of those with Category 3, 35.9% of those with Category 4, and 10.3% of those with Category 5. Regarding the morphology and distribution of microcalcifications, breast cancer accounted for 46.2%, 5.1%, 2.6%, 35.9%, 7.7%, and 2.6% of the cases with small round/clustered, amorphous/clustered, pleomorphic/clus- tered, pleomorphic/linear segmental, and fine linear/clustered patterns, respectively. Also, we examined each of the patients, (1) who underwent mammography for medical examinations, (2) who underwent mammography performed at other institutions, (3) who underwent follow-up for microcalcifications and postoperative follow-up mammography. The proportions of breast cancer diagnoses were (1) 11.4%, (2) 20.6%, and (3) 7.1%. Proportions of Category 3 breast cancer were (1) 10.3%, (2) 38.5%, and (3) 5.1%. Among the cases in which ST-MMT was performed in this study, Category 3 accounted for more than half. However, 10.9%(21/192 lesions)were diagnosed as malignant in Category 3. The diagnosis of breast cancer in pa- tients who underwent mammography performed at other institutions was not observed in 79.4%(104/131 lesions), and among the 104 lesions, as a result of reassessment of calcification in our hospital, Category 2 was also included. Calcification in Category 2 lesions was benign in all cases. It was suggested that the indication for ST-MMT biopsy could be further narrowed down by being careful not to over-diagnose.